Carvidelol Vs Propanol for Secondary Prophylaxis of Variceal Hemorrhage in Liver Cirrhosis Patients : Efficacy of Carvedilol Vs Propranolol - Sohail, Muhammad; Kamran, .; Sajjad Khan, Muhammad; Irshad, Zainab; Fahim, Muhammad; Naeem, Sundus; Ullah, Inam; Rubina Gillani, Syeda (Pakistan Journal of Health Sciences, 2023)
Propranolol and Carvedilol are the currently used medications for main prophylaxis of variceal bleeding. Objective: To investigate the efficacy of carvedilol vs propranolol for prevention of variceal hemorrhage in liver cirrhosis patients. Methods: This prospective comparative study was carried out on 196 cirrhotic patients in the Gastroenterology Department of Lady Reading Hospital, Peshawar in collaboration with Pharmacology department of Khyber Medical University, Peshawar from July 2018 to June 2020. Patients with no prior history of primary variceal prophylaxis treatment and variceal bleeding were enrolled. All the patients were categorized into two groups: Group-I (Carvedilol) and Group-II (propanol). Frank hematemesis, melena, and endoscopic assessment was used for the evaluation of variceal bleeding. Results: Of the total 196 liver cirrhosis patients, Group-I and Group-II had 102 (52%) and 94 (48%) respectively. Ultrasonography found splenomegaly in 88% of cases and moderate to severe ascites in 42.6% of the patients investigated. The success rate of carvedilol and propanol group was 76% and 64.8% respectively. The side-effects and complication rate were significantly lower in Group-I than Group-II. The prevalence of variceal bleeding was 16.7% (n=17) and 11.7% (n=11) respectively. Conclusions: Carvedilol is an excellent treatment alternative for prevention of variceal bleeding than propranolol in terms of side-effects and complications rate.